(untitled) (Al-Academy, 2023)
The subject of the tagged research (becoming and integration of the film in postmodern cinema) is summarized by studying the transformations and complementarity of the film in light of the emergence of the concern of postmodernism. Then the need for it, as well as the objectives of the research and clarify its limits, as well as its importance. Then the transition to the theoretical framework, which included two sections, the first topic was entitled: Postmodern Cinema Formation and Completion, while the second topic was entitled: Paradox in Postmodern Film. After completing the theoretical aspect, the research concluded with a number of theoretical framework indicators that were adopted as a tool for analyzing the sample, then the research procedures came, represented in the analysis of the research sample, which is the movie (New York Stories) directed by: Martin Scorsese to come up with the results of the analysis and then the conclusions and recommendations, then came the list of sources and margins.